Pengaruh Pendidikan Dan Pendapatan Per Kapita Terhadap Kemiskinan Di Provinsi Aceh - Sumono; Wayus, Dicky; Asnidar; Hanum, Nurlaila; Andiny, Puti; Safuridar (Shofanah Media Berkah, 2024)
This study aims to examine the effect of education and per capita income on the poverty rate in Aceh Province during the period 2010 to 2023. The level of education is measured through average years of schooling, while per capita income reflects the economic welfare condition of the community. Secondary data in this study were obtained from the Central Bureau of Statistics (BPS) and analyzed using multiple linear regression method. The results show that education has a negative and significant influence on poverty, while per capita income shows a positive but insignificant influence. Overall, these two variables have a significant influence on poverty in Aceh Province. This shows the importance of increasing access to education and improving income distribution to reduce poverty. However, increasing per capita income alone is not effective enough if it is not accompanied by equal distribution and improved quality of education. The coefficient of determination (R²) for the variables of education and per capita income on poverty in Aceh Province is 92.41%, while the rest is influenced by other factors outside the variables of this study.